Edukacja czy propaganda? Sztuki plastyczne w kręgu mecenatu artystycznego Stanisława Augusta Poniatowskiego - Dormus, Katarzyna (Biuletyn Historii Wychowania, 2026)
The arts towards the end of the 18th century – the period of Stanislaw August rule (1764–1795) – developed in very difficult times of failing Polish statehood. In an attempt to preserve the independence of the Polish-Lithuanian Commonwealth, the king pursued a consistent modernization agenda in a variety of areas. The proposed reform program required, however, mindset changes across the society. As an enlightened ruler, Stanislaw August believed in the educational and propaganda benefits of the arts, with the ultimate goal of serving the national interest and strengthening the commonwealth. The room decorations in the Royal Castle in Warsaw and the Palace on the Isle in the Royal Łazienki represent the best examples of the king’s efforts in this area.